Improved Patient Satisfaction following Robotic-Assisted Total Knee Arthroplasty - Smith, Austin F.; Eccles, Christian J.; Bhimani, Samrath J.; Denehy, Kevin M.; Bhimani, Rohat B.; Smith, Langan S.; Malkani, Arthur L. (The Journal of Knee Surgery, 2019)
Approximately 20% of the patients are dissatisfied with their total knee arthroplasty (TKA). Computer technology has been introduced for TKA to provide real time intraoperative information on limb alignment and exact flexion/extension gap measurements. The purpose of this study was to determine if patient satisfaction could be improved with the use of robotic-assisted (RA) technology following primary TKA. A total of 120 consecutive patients undergoing RA-TKA with real time intraoperative alignment and gap balancing information were compared with a prospective cohort of 103 consecutive patients undergoing TKA with manual jig-based instruments during the same time period. There were no differences between groups with age, gender, baseline Knee Society Score (KSS) knee and function scores, follow-up, and ASA scores. TKAs were performed using same technique, implant design, anesthesia, and postoperative treatment protocols. Patient satisfaction survey using KSS and Likert scoring system were obtained at 1-year follow-up. Likert scoring system demonstrated 94% of the patients in the RA group were either very satisfied or satisfied versus 82% in the manual instruments TKA group (p = 0.005). RA-TKA group had better average scores of all five satisfaction questions although not significant. RA-TKA group had a better average overall satisfaction score of 7.1 versus 6.6 in the manual instrument group, p = 0.03. KSS function scores were significantly better at 6 weeks and 1 year postoperatively (p = 0.02, 0.005), and KSS knee scores were significantly better at 1 year postoperatively (p = 0.046). There are multiple reasons for patient dissatisfaction following primary TKA. Using intraoperative computer technology with RA surgery for patients undergoing a primary TKA, a significant improvement in patient satisfaction was demonstrated compared with TKA using conventional manual jig-based instruments. RA surgery provides several advantages in TKA including real time information in millimeters to help obtain balanced gaps, accurate bone cuts, reduced soft tissue injury, and achieve the target alignment which may lead to improved patient satisfaction.
Keywords: total knee arthroplasty; robotic-assisted; patient satisfaction; outcomes